Aplicações da função de Euler - Piffer, Anderson Marcos (2014)
Currently there is a gap to be filled by the students in Mathematics: The gulf between the proposed innovative methodologies in disciplines related area of mathematics education and the traditional method with which to develop subjects worked in other university courses. Many of these students, who throughout the elementary and high school, have not had the opportunity to deal with mathematics in context, remain deprived of this experience in college. Even theoretically aware of the need to innovate, many of these students when teachers end up playing with your students what they experienced over virtually the entire academic training. On the other hand, is not always easy for the professor to address to- pics of abstract algebra, among others, in a way that arouses the investigative spirit of the student. There is a tendency in our academic culture, to present the theorems followed by statements, which are not sufficient to explain the underlying motivations, nor the implications of the results mentioned. We believe it is necessary to act at different levels of education, with the goal of making the teaching and learning of mathematics and more inquisitive facing reflection. In this context, we are researching methodologies in which students are led to investigate the applicability of some of these mentioned mathematical concepts are part of the Degree in tem ́atica. Apresentaremos this paper the results we obtained involving Research the number of digits of the period of regular tithes and very current theme of RSA encryption.